Effect of different solutions on color stability of acrylic resin-based dentures. - Goiato, Marcelo Coelho [UNESP]; Nóbrega, Adhara Smith [UNESP]; dos Santos, Daniela Micheline [UNESP]; Andreotti, Agda Marobo [UNESP]; Moreno, Amália [UNESP] (My University, 2014)
The aim of this study was to evaluate the effect of thermocycling and immersion in mouthwash or beverage solutions on the color stability of four different acrylic resin-based dentures (Onda Cryl, OC; QC20, QC; Classico, CL; and Lucitone, LU). The factors evaluated were type of acrylic resin, immersion time, and solution (mouthwash or beverage). A total of 224 denture samples were fabricated. For each type of resin, eight samples were immersed in mouthwashes (Plax-Colgate, PC; Listerine, LI; and Oral-B, OB), beverages (coffee, CP; cola, C; and wine, W), and artificial saliva (AS; control). The color change (DE) was evaluated before (baseline) and after thermocycling (T1), and after immersion in solution for 1 h (T2), 3 h (T3), 24 h (T4), 48 h (T5), and 96 h (T6). The CIE Lab system was used to determine the color changes. The thermocycling test was performed for 5000 cycles. Data were submitted to three-way repeated-measures analysis of variance and Tukey's test (p<0.05). When the samples were immersed in each mouthwash, all assessed factors, associated or not, significantly influenced the color change values, except there was no association between the mouthwash and acrylic resin. Similarly, when the samples were immersed in each beverage, all studied factors influenced the color change values. In general, regardless of the solution, LU exhibited the greatest DE values in the period from T1 to T5; and QC presented the greatest DE values at T6. Thus, thermocycling and immersion in the various solutions influenced the color stability of acrylic resins and QC showed the greatest color alteration.